2015
DOI: 10.3389/fenrg.2015.00015
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Microalgae Biomass and Lipid Stability Post-Cultivation

Abstract: Processing of microalgal biomass to biofuels and other products requires the removal of the culture from a well-controlled growth system to a containment or preprocessing step at non-ideal growth conditions, such as darkness, minimal gas exchange, and fluctuating temperatures. The conditions and the length of time between harvest and processing will impact microalgal metabolism, resulting in biomass and lipid degradation. This study experimentally investigates the impact of time and temperature on Nannochlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Lipid content remained constant for the anaerobic and sulfuric acid treatments at 10–10.7%. This is consistent with reported lipid stability in Tetraselmis suecica stored at 4 °C over a 90-day period, and Nannochloropsis salina stored at 4 °C and 40 °C over a 6-day period [24, 25]. In contrast, the lipid content increased as a fraction of the total biomass for the glycosidase (11.8–12%) and glucose oxidase treatment (13.5–13.7%) after 30 and 180 days of storage due to the loss of other biomass constituents.…”
Section: Resultssupporting
confidence: 90%
“…Lipid content remained constant for the anaerobic and sulfuric acid treatments at 10–10.7%. This is consistent with reported lipid stability in Tetraselmis suecica stored at 4 °C over a 90-day period, and Nannochloropsis salina stored at 4 °C and 40 °C over a 6-day period [24, 25]. In contrast, the lipid content increased as a fraction of the total biomass for the glycosidase (11.8–12%) and glucose oxidase treatment (13.5–13.7%) after 30 and 180 days of storage due to the loss of other biomass constituents.…”
Section: Resultssupporting
confidence: 90%
“…Also the lipid content on percent dry weight basis varied significantly (p ≤ 2.44 x 10 -8 ) among the macroalgae species assessed. The differences in lipid content of algal species, according to Napan et al, (2015) could be attributed to the inherent lipid accumulation capacities of the different species. Also when algae species are starved, that is, deprived of nitrogen, the amount of oil produced increases (Napan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Since no severe cell disruption was observed for the algae paste stored at 4°C, centrifuge would not have caused the high mortality and disruption rate of algae paste stored at 20°C. At 20°C or 4°C, when stored under sealed dark, aerobic respiration decreases due to the exhaustion of oxygen and accumulation of carbon dioxide (Napan et al, 2015), and algae mortality increases. In this case, the anaerobic cellular respiration will also occur with the bacteria and/ or archaebacteria available.…”
Section: Viability and Morphologymentioning
confidence: 99%
“…Temperature affects the activity of the enzyme and the subsequent enzyme-driven processes. It has been reported that the lipid degradation rate increased with storage temperature (Balduyck et al, 2016;Napan et al, 2015). For some alga species, lipid content remained unchanged under freezing conditions for as long as 21 months, or under refrigeration (1°C or 4°C) for a short period (from 1 week to 3 months) (Montaini et al, 1995;Napan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%